Calculations of Performance Characteristics of Submerged Cargo Pumps with Hydraulic Drive and Constant Torque Controllers, Taking into Account the Energy Efficiency of the Drive Motor - Andrzej Banaszek (Energies)
Submerged cargo pumps installed on board tankers are one of the most important components of their cargo system. As they are installed directly in the cargo tanks, they are usually equipped with a hydraulic drive whose power and capacity are controlled by constant-torque controllers. These have a significant impact on the technical and performance characteristics of the cargo pumps. This paper presents a methodology for calculating the performance characteristics of submerged cargo pumps, taking into account the energy efficiency of their hydraulic drive motors. Due to their number and power, the cargo pumps are powered from the ship’s hydraulic central loading system. This paper describes the main parts of the hydraulic power system structure and the functions of the constant torque controller of the STC type. A mathematical model has been developed to use the basic characteristics of submerged cargo pumps made for the base cargo (water) sent by the pump manufacturer for the case of handling liquid cargo with different parameters. The model considers the characteristics of the hydraulic drive, including a Bosch Rexroth A2FM type hydraulic drive motor and a constant torque controller. The results of simulation calculations of the performance characteristics of an example cargo pump are presented and compared with measurements of the characteristics of this pump on a product tanker. The mathematical model presented in this paper is of utilitarian value, enabling calculations to be carried out without the need for time-consuming CFD numerical methods, making it useful for port and fuel terminal logistics services, ship crews and services managing the operation of product tanker fleets.